Rancangan Pembangkit Listrik Tenaga Angin dan Surya dengan Turbin Angin Sumbu Vertikal Savonius Menggunakan Bentuk Sudu L dengan Kapasitas Daya Sebesar 746,5 Wh - Wahyudi, Deni; Rollastin, Boy; Pranandita, Nanda (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The design of wind and solar power generators is the goal of utilizing solar thermal energy and wind speed on the coast. To get a design result that is in accordance with the power requirement of 720 W, therefore the results of this design have followed the steps in the VDI 2222 method. From the results of the calculations that have been carried out the Savonius type wind turbine uses an L-shaped profile, with a diameter of 710 mm and a height 592 mm can produce a power of 279.072 Wh. And for the power generated from a Polycrystalline type of solar panel with a capacity of 50 Wp as much as 1 unit can produce a power of 467.5 Wh. Based on the calculation results of the combination of wind turbines and solar panels, a power of 746.6 is obtained. So that with this power it meets the capacity of the power requirement of 720 Wh. From the results of the calculation of the strength analysis of the material on the turbine shaft with material type SS 304 using SolidWorks software, it is known that the allowable stress on the material SS 304 is 200 MPa, then the resultant torsional stress with a load of 1217 Nm produces a yield strength of 1.723e+002 N/mm2(MPa), and the max torsional stress is 1.723e+000N/ mm2 (MPa).